A state wide validation and utilisation study of the Queensland emergency nursing workforce tool. (23rd July 2013) - Williams, Ged; Crilly, Julia; Souter, Jeffrey; Veach, Kate; Good, Norm
<x xml:space="preserve">Abstract</x> Aim To describe and compare standard practice with a revised, assisted method for calculating emergency department nursing workforce requirements (using the emergency nursing workforce tool, ENWT) within 27 Queensland public hospital emergency departments (ED). Background Despite the presence of several methodologies used for staffing calculations, there is a necessity to refine measures of emergency department complexity and workload to determine appropriate staffing in order to meet patient safety needs and health service key priority indicators. Methods A descriptive comparative study design was employed. Of the 27 ED nurse unit managers (NUM) invited, 18 (67%) participated. Results No significant difference was noted in the full time equivalent (FTE) nursing requirement when standard vs. new (ENWT) methods were compared. The ENWT was more efficient (i.e. timely) and had better predictability than existing methods for calculating FTE nursing requirement. Conclusion The methodology underpinning the ENWT may be useful to apply or adapt to settings other than the ED (e.g. intensive care, operating room) and disciplines within the ED other than nursing (e.g. medicine, allied health, porterage) to inform staffing requirements. Implications for nursing management Findings from this research can be used to inform ED managers and health service planners regarding a standardized approach to calculating emergency nursing workforce needs.